Analysis of the Effectiveness of Motor Vehicle Insurance at PT. Jasa Raharja: - Rozy, Fachrul; Harmain, Hendra; Nasution, Juliana (ProBisnis : Jurnal Manajemen, 2023)
This study aims to test the analysis of the effectiveness of motor vehicle insurance at PT. Jasa Raharja branch Medan. Insurance at PT. Jasa Raharja Motor are an effort to protect citizens, especially from the risk of road traffic accidents, to provide compensation to victims of traffic accidents or to their heirs. This research took 4 respondents, consisting of 1 employee PT. Jasa Raharja, and 3 people who were victims of traffic accidents, and received compensation funds. This method uses interview techniques. The interview technique was carried out in an unstructured manner using an interview guide. Research data analysis is descriptive. The results of this research indicate that PT. Jasa Raharja still seems to be good and consistent in carrying out its duties as a fund collector and distributor of traffic accident compensation funds. Traffic accident victims and recipients of compensation funds revealed that PT. Jasa Raharja is satisfied with the services provided. The benefits obtained at PT. Jasa Raharja are indeed effective and efficient because they have achieved the targets desired by PT. Jasa Raharja Branch Medan.